Vestibular Evoked Myogenic Potential: We Propose a New Instrument - de Oliveira, Aline Cabral; Colafêmina, José Fernando; Menezes, Pedro de Lemos (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: Currently, there is still no specific instrument for assessment of vestibular evoked myogenic potentials, with the same performed by a device designed to capture auditory evoked potentials available in the market. Thus, the functions of amplification, filtering, stimulation, window capture, rejection of artifacts and features of averaging, as well as its management software, are much to be desired for the new role assigned to it.Objective: To compare latencies and amplitudes of components p13 and n23, and the indices of asymmetry between a devices considered the gold standard (EP25), adapted to record the potential and the new equipment developed.Method: An experimental study with 11 normal hearing. From the tone-burst sound stimuli of 10 ms, frequency of 500 Hz with intensity 90 dBNAn, evoked myogenic potentials were recorded with 80 ms windows.Results: You can see no significant differences when comparing the two instruments regarding the parameters of latency and amplitude, except for the latency of n23, with p = 0.005. The value of asymmetry index inter-p13-n23 peak for the new unit (20.1%) was significantly lower than that found for the EP25 (30.5%), with p less than 0.01.Conclusion: Thus, we conclude that there are no differences for the latencies and amplitudes of VEMP between the EP25 and the new device developed by presenting the latter, closer to the values reported in literature and a lower index of asymmetry of amplitude between p13-n23 peak. Study form: Prospective clinical and experimental. Identifier: NCT01132105.
Keywords: evoked potentials; vestibule; labyrinth; diagnosis